2016
DOI: 10.4102/ojvr.v83i1.1083
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report on osteochondrosis in cattle in the north-western parts of South Africa

Abstract: The north-western part of South Africa, in particular, is well known for mineral imbalances. Aphosphorosis, resulting in rickets and osteomalacia, received a lot of attention at the turn of the nineteenth century (1882–1912). This was followed in 1997 by research on Vryburg hepatosis, another area-specific mineral imbalance–related disease in young calves reared on manganese-rich soil derived from the weathering of dolomitic (carbonate) rock formations. In 1982, a totally new syndrome (osteochondrosis) manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…The fact that none of the study cattle responded positively to any of the supplementations, regardless of different micro- and macromineral level intake between sub-groups, warranted further investigation. The results obtained in this study are contradictory to those observed during the 2012 pre-trial where cattle fed a supplement containing high levels of both micro- and macrominerals responded positively with a marked decrease in the severity of lameness and size of the peri-articular swelling (Prozesky et al 2016 ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The fact that none of the study cattle responded positively to any of the supplementations, regardless of different micro- and macromineral level intake between sub-groups, warranted further investigation. The results obtained in this study are contradictory to those observed during the 2012 pre-trial where cattle fed a supplement containing high levels of both micro- and macrominerals responded positively with a marked decrease in the severity of lameness and size of the peri-articular swelling (Prozesky et al 2016 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The size of the peri-articular swelling and the degree of lameness of the trial cattle were used to determine the effect of the supplements. Visual grading of lesions has been statistically proven to be a valid method (unpublished data: K. Botha, 2016 ). Analysis of the initial values for all the cattle indicated that there were no significant differences pertaining to the sex, age, weight, lameness score, acute peri-articular swelling score, chronic peri-articular swelling (fibrosis) score and the overall disability score.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations